Serum Levels of Protein Z, Laminin Subunit Alpha 2, Mixed Lineage Leukemia 4, and Plexin Domain Containing 2 in Newly Diagnosed and Metformin-Treated Type 2 Diabetes Patients - Sami, Sarah Sameer; Taha , Ekhlass M. (Iraqi Journal of Science, 2024)
Diabetes mellitus is a globally prevalent disease with several parameters that may be involved in diagnosis or altered throughout disease progression. In this study, 120 patients with type 2 diabetes and healthy controls were recruited, with ages ranging from 30-65 years old. The research focused on determining levels of Protein Z (PROZ), Laminin Subunit Alpha 2 (LAMA2), Mixed Lineage Leukemia 4 (MLL4), and Plexin Domain Containing 2 (PLXDC2). Participants were divided into four groups: group I (n=30) with long-term metformin treatment, group II (n=30) with short-term metformin treatment, group III (n=30) newly diagnosed without medication, and group IV (n=30) healthy controls. Protein markers were measured by ELISA, while fasting blood glucose, lipid profiles, and HbA1c were determined by spectrophotometry and HPLC. ROC curve analysis revealed PLXDC2 had high sensitivity and specificity as a potential biomarker for diabetes diagnosis. LAMA2, MLL4, and PROZ also distinguished between diabetes patients and controls. Overall, these results identify promising biomarkers for diabetes detection and monitoring.